XBT operational best practices for quality assurance - Justine Parks; Francis Bringas; Rebecca Cowley; Craig Hanstein; Lisa Krummel; Janet Sprintall; Lijing Cheng; Mauro Cirano; Samantha Cruz; Marlos Goes; Marlos Goes; Shoichi Kizu; et al. (Frontiers in Marine Science, 2022)
Since the 1970s, eXpendable BathyThermographs (XBTs) have provided the simplest and most cost-efficient solution for rapid sampling of temperature vs. depth profiles of the upper part of the ocean along ship transects. This manual, compiled by the Ship of Opportunity Program Implementation Panel (SOOPIP) a subgroup of the Global Ocean Observing System (GOOS) Observations Coordination Group (OCG) Ship Observations Team (SOT) together with members of the XBT Science Team, aims to improve the quality assurance of XBT data by establishing best practices for field measurements and promoting their adoption by the global operational and scientific community. The measurement system components include commercially available expendable temperature probes, the launcher, the data acquisition (DAQ) hardware, a Global Navigation Satellite System (GNSS) receiver, an optional satellite transmitter, and a computer with software controls. The measurement platform can be any sea-going vessel with available space for the equipment and operator, and capable of oceanic voyages across the regions of interest. Adoption of a standard methodology in the installation and deployment of the measurement system will lead to data quality improvements with subsequent impact on the computation and understanding of changes in the near surface ocean properties (e.g., heat content), ocean circulation dynamics, and their relationship to climate variability.